Building on the Past: Enacting Established Personal Identities in a New Work Setting - Beyer, Janice M.; Hannah, David R. (Organization Science, 2002)
A qualitative, longitudinal study of two groups of experienced professionals beginning work in a research organization provided insights into how newcomers with work experience adjust to and become assimilated into new jobs and work settings. Multiple methods were used to collect data on the newcomers' work experiences before and after assuming their new jobs. Repeated interviews with them during their first six months in their new jobs revealed that their past experience affected their assimilation in three primary ways: through the personal identities they had developed and carried with them, through the know-how they had acquired in past jobs and how well it fit with their new jobs, and through the personal tactics they had learned for managing their work and managing change. In general, newcomers with diverse experience adjusted better than those with narrow experience because (1) they found it easier to enact dimensions of their personal identities that allowed them to function effectively in the new situation, (2) they more easily found a fit between know-how gleaned from that experience and their new jobs, and (3) they could draw on a wider variety of personal tactics that they had previously used to help them adjust.